Digital Competences in Secondary Education Teachers in a Province of Central Peru - Orosco-Fabian, Jhon Richard; Pomasunco-Huaytalla, Rocío; Gómez-Galindo, Wilfredo; Salgado-Samaniego, Edwin; Colachagua-Calderón, Deysi Alina (Revista Electrónica Educare, 2021)
Objective: Analyze the level of achievement of digital competencies in secondary education teachers according to gender, age, and working conditions. Method: The research has a quantitative approach and a descriptive cross-sectional design. The sample consisted of 247 teachers from public educational institutions of a province in the central region of Peru. Information was collected through an elaborated instrument based on the proposal of the Intef (2017) that assesses digital competencies grouped into five areas. Results: The results show that teachers have a satisfactory level of achievement in the digital competencies of Internet navigation, search and filtering of information, data and digital content (50.2%), development of digital content (42.5%), curriculum integration (46.2%), and health protection (44.9%). In the other digital competencies, teachers have a level of achievement in progress. Conclusions: It is concluded that teachers are in the process of developing digital competencies, and there is a significant difference in relation to the variables of gender, age, and working conditions.